2003
DOI: 10.1182/blood-2002-11-3451
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase and telomere length in multiple myeloma: correlations with disease heterogeneity, cytogenetic status, and overall survival

Abstract: We have investigated the significance of telomerase activity (TA) and telomere length (TL) in multiple myeloma (MM). The analyses were undertaken on CD138 ؉ MM cells isolated from the marrow of 183 patients either at diagnosis or in relapse. There was heterogeneity in telomerase expression; 36% of the patients had TA levels comparable to those detected in normal plasma cells, and 13% of patients had levels 1-to 4-fold greater than in a neuroblastoma cell line control. The TL of MM cells was significantly short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
64
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 49 publications
14
64
1
1
Order By: Relevance
“…Aging of leukocytes reflected by short telomere length may impair immune surveillance and reduce the clearance of tumor cells. A study demonstrated that patients with multiple myeloma with high telomerase activity and short telomere length presented a poor prognosis (Wu, Orme et al 2003). Accordingly, another study reports the same results in adult T-cell leukemia, suggesting that telomerase www.intechopen.com activity and low telomere content may be novel markers for the prognosis of these diseases (Kubuki, Suzuki et al 2005).…”
Section: Blood Telomere Length As a Potential Predictor For Cancer Risupporting
confidence: 54%
“…Aging of leukocytes reflected by short telomere length may impair immune surveillance and reduce the clearance of tumor cells. A study demonstrated that patients with multiple myeloma with high telomerase activity and short telomere length presented a poor prognosis (Wu, Orme et al 2003). Accordingly, another study reports the same results in adult T-cell leukemia, suggesting that telomerase www.intechopen.com activity and low telomere content may be novel markers for the prognosis of these diseases (Kubuki, Suzuki et al 2005).…”
Section: Blood Telomere Length As a Potential Predictor For Cancer Risupporting
confidence: 54%
“…24 The only prospective study evaluating lymphoma risk in relation to TL 23 suggested that individuals with relatively longer telomeres have an elevated NHL risk which is inconsistent with the results of previous case-control studies. 22,25 As such, the finding in the prospective cohort study deserves further follow-up to see if these findings can be corroborated in an independent study.…”
Section: Epidemiologymentioning
confidence: 72%
“…case-control studies among MM (n 5 183) 25 and CLL patients (n 5 70) 35 did not show significant TL differences between patients and healthy controls. These studies were limited by small control groups (seven MM studies and 15 CLL studies) and possibly confounded by the inclusion of pretreated patient subgroups (MM study).…”
Section: Epidemiologymentioning
confidence: 84%
“…TL in MM cells has been shown to be reduced compared to patient-matched leucocytes and normal age-matched controls, and was shorter still in patients with relapsed disease (Cottliar et al, 2003;Wu et al, 2003). In addition, there appears to be a stabilization of telomeres in the shorter length ranges below 5AE5 kb.…”
Section: Multiple Myeloma (Mm)mentioning
confidence: 96%